Avaliação dos pesos regionais do RTQ-R a partir da análise da estrutura do consumo residencial de energia elétrica por região geográfica - Karla Cristina de Freitas Jorge Abrahao (2015)
This study is part of a large area of knowledge in Social Sciences, the Architecture and Urbanism Technology sub area, the residential electricity consumption by Brazilian geographic region, and Brazilian regulations for energy efficiency in the residential buildings (RTQ-R) context. The study starts from the linear geometric growth analyses, then determine the premise that the socioeconomics scenarios that influenced the residential electricity consumption between years 2005 to 2012, as the electricity supply will continue until the year 2020. The importance of this study refers to the contribution to the improvement of RTQ-R, based on an analysis of the future residential electricity end use estimates, by Brazilian geographic region. Then, the main hypothesis regarded in this study is that RTQ-R can be improve by accurately regionals aspects. The residential electricity consumption by geographic regions is variable being influenced by different scenarios such as regional social, political, economical and climate. Then, the understanding of this dynamic over the years, has had a great importance to guide the planning of energy resources and energy efficiency policies. This study describes the residential electricity consumptions scenarios in recent years in Brazil. The main objective of this study is to determine the Brazilian residential energy consumption structure, by region over time, and examine in which aspects of residential electricity consumption the RTQ-R could be increased from a regional approach and an end-use forecast. The method used in this study starts creating a database from official sources, and applying a methodology already used in other studies. The study estimated the residential electricity consumption structure for the year 2005, and the consumption structure extrapolations to the years 2015 and 2020. A comparative analysis of the residential electricity consumption structure, between the years 1995, 2005, 2015 and 2020, enabled the understanding of the residential electricity end use evolution over the years. Based on the results estimated for the year 2020, an analysis was done of the RTQ-Rs regional weights, and later the development of suggestions for changes in the RTQ-R regulation. The estimated participation of end use consumption by the environmental comfort appliances group , to the year 2020, for the North, Northeast and Midwest, was respectively 50.9%, 34.9% e 26.8%, In the Southeast and South regions these parcels were respectively 15.1% e 17.9%. The changes proposed to improve aspects of the RTQ-R relate to: the numerical envelope equivalent (EqNumEnv) in the North, Northeast and Midwest; the air conditioning and ceiling fans installation bonus points in all regions; the numerical water heating system equivalent (EqNumAA) in the Northeast, when there is no existing water heating system declared. It is suggested, through the presentation of a new equation, that the envelope efficiency to cool bedrooms, in the North, Northeast and Midwest, can directly participate in the envelope performance of the housing unit. Also, within the air conditioning bonus context, it is suggested to change the relative bonus points on a new scale, respectively up to 0.4 points and up to 0.2 points, according to geographical region and EqNumEnv level. It is also suggested the expansion of the air conditioning bonus, in the Southeast and South, so that buildings with EqNumEnv level B and C are eligible to gain bonus points. It is suggested for all regions the increase valuation of the bonus points for ceiling fans installation for up to 0.4 points. In the context of residential buildings in the Northeast, that do not have installed water heating systems declared, it is suggested that it is assigned a value of level 1 (one) for EquNumAA, as with the Midwest, Southeast and South regions. The conclusive analyses led to the observation that some regions have a tendency to increase in electricity consumption in certain groups of appliances, more than others, The great contribution of this study is in the energy efficiency science in Brazil, particularly on the regional aspects of RTQ-R, in which an upgrade in some of its requirements and criteria would be of great relevance.